BAS/BSCR6 α-Ketoglutarate: biological effects of a novel biomarker of heart failure. Issue 17 (26th August 2010) - Nikolaidou, T; Mamas, M; Oceandy, D; Neyses, L
Abstract : Heart failure is often associated with renal impairment (cardiorenal syndrome). Using a metabolomics approach, our group identified α-ketoglutarate as a novel metabolite that was significantly elevated in patients with heart failure.1 It was as strongly associated with heart failure as the 'gold-standard' biomarker brain natriuretic peptide. α-Ketoglutarate is a citric acid cycle intermediate, central in cardiac energy production. It is the ligand of GPR99, a G-protein coupled receptor mostly expressed in the kidney.2 In HEK 293 cells, GPR99 acted through a Gq-mediated pathway to increase intracellular calcium. Importantly, we found that the GPR99 receptor is present in neonatal rat cardiomyocytes (NRCM). We tested the expression of 84 genes previously known as regulators of angiogenesis in NRCM treated with 1 mM α-ketoglutarate. Using real-time PCR, we found significant increase in the expression of VEGF receptor-1 and placental growth factor, suggesting a possible effect of α-ketoglutarate in the regulation of angiogenesis and growth. These findings show that binding of α-ketoglutarate to the GPR99 receptor in the heart leads to activation of the Gq pathway and causes upregulation of VEGFR1 and placental growth factor. This might have a role in vascular adaptation to hypertrophy. In addition, in vivo animal studies have previously shown that protein kinase C has a role in renal dysfunction. This leads to the novel and testable hypothesis that α-ketoglutarate also contributes to the development of the cardiorenal syndrome.